Agama Dalam Mengantisipasi Singularitas Teknologi - Najoan, Denny (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2022)
Throughout human civilization, technology has always been attached to humans as a device. This device makes humans’ life easier and safer. However, in subsequent technological developments, humans have lost their fundamental nature. Technology has started to switch humans’ consciousness in understanding oneself and God, the creator of the universe. Humans have started to make technology as their gods and it dominates humanity. When technology has been completely made into a god, this is called a technological singularity. Using the method of literature review, this article descriptively explains that religion has a role in anticipating technological singularities. Religion describes that technology is not despised by God. In several biblical stories, God asks humans to use technology to build good relationships between humans and God and each other. Technology must be a tool for humans to glorify God and also build relation with fellow humans and other creatures. The relationship between humans and technology is not meant to destroy the relationship between humans and God, but to strengthen it. With such an understanding, religion understands that technology is God's will to help humans strengthen their relationship with God and His other creations.